Swelling of the Leg, Deep Venous Thrombosis and the Piriformis Syndrome - Sara Bustamante; Peter G Houlton (Pain Research and Management)
BACKGROUND: The piriformis syndrome, which was first described 60 years ago, is a well recognized cause of sciatica, leg pain and low back pain, due to the entrapment of the sciatic nerve in the piriformis and other rotator muscles. Very few complications relating to this syndrome have been described.